Analysis of platelet α2-adrenergic receptor activity in stable coronary artery disease patients on dual antiplatelet therapy - Béres, Bernát János; Tóth-Zsámboki, Emese; Vargová, Katarína; László, Ádám; Masszi, Tamás; Kerecsen, Gábor; Préda, István; Kiss, Róbert Gábor (Thrombosis and Haemostasis, 2008)
Combined antiplatelet therapy reduces recurrent atherothrombotic events in stable coronary disease patients; however, high residual platelet reactivity measured ex vivo still raises concerns as a condition related to treatment failure. Alpha-2 adrenoceptor enhances platelet reactivity and might contribute to this phenomenon. For the present study, 121 stable angina patients on standard dual antiplatelet therapy (75 mg clopidogrel and 100 mg acetylsalicylic acid) were recruited. Born aggregometry was performed with adenosine diphosphate (ADP),collagen and epnephrine. To verify platelet adrenergic activity, potentiation by low-dose epinephrine and inhibition by selective alpha-2 receptor blocker atipamezole were determined. To assess the P2Y12-specific residual activity, cangrelor was used. Plasma norepinephrine, soluble CD40-ligand, high-sensitivity-C-reactive protein (hsCRP) - and in 24 subjects platelet P-selectin positivity were measured. Epinephrine - at very low concentration (10-9g/ml) - significantly potentiates (1.25 µM ADP: 26.5% vs. 43%; 5 µM ADP: 53% vs. 64.5%; collagen: 17% vs 42%, p<0.001) while atipamezole inhibits ADP- and collagen-induced platelet aggregations (1.25 µM ADP: 26.5% vs. 23%; 5 µM ADP: 53% vs. 47%;collagen:17% vs.11%,p<0.001).Patients with high adrenergic activity have significantly increased baseline ADP- and collagen-induced platelet aggregation. Based on cangrelor’s efficacy, these patients have significantly more residual P2Y12 activity as well.HsCRP and soluble CD40-ligand levels were similar.In conclusion, stable coronary heart disease patients with prominent adrenoceptor activity in vitro have significantly increased platelet aggregability and more functional P2Y12 receptor, indicating poor inhibitory response to thienopyridines.Therefore,platelet adrenergic receptor represents a considerable, dynamic factor of high residual platelet reactivity and might contribute to cardiovascular events indicating failure of antiplatelet therapy.
Keywords: Antiplatelet agents; cardiology; platelet physiology; receptors